Electrical Resistivity of Ca, Ba-Doped Lead Molybdate Ceramics - Singh, N.K. (Asian Journal of Chemistry, 2010)
Polycrystalline samples of Pb1-x RxMoO4 (x = 0.00; 0.05; 0.10; 0.15 and R = Ca, Ba) were prepared using solid-state reaction technique. Detailed studies of dc resistivity as function of biasing electric field (0.5 to 9.2 kV/m) and temperature (304-573 K) indicate that the compounds have non-ferroelectric properties but contain space charge polarization at high temperatures.